2018
DOI: 10.1007/s13340-018-0360-4
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone use and risk of bladder cancer: a systematic literature review and meta-analysis of observational studies

Abstract: Background Studies investigating bladder cancer risk in pioglitazone-treated type 2 diabetes mellitus patients report conflicting results. Previous meta-analyses on this topic utilized publications prior to 2013. More long-term observational studies have been published since then. We reviewed the accumulated evidence and updated findings from previous meta-analyses. Methods This meta-analysis was based on a systematic review of peer-reviewed observational studies published prior to September 30, 2016. Eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…A prospective study from Kaiser Permanente database has found that pioglitazone use is not associated with increased risk of bladder cancer [62]. Although there is a possible association between bladder cancer and pioglitazone, the causality is not definitely proven considering results from the most recent meta-analysis [63]. These new studies suggest that the association of bladder cancer with pioglitazone might be due to ascertainment bias [64].…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…A prospective study from Kaiser Permanente database has found that pioglitazone use is not associated with increased risk of bladder cancer [62]. Although there is a possible association between bladder cancer and pioglitazone, the causality is not definitely proven considering results from the most recent meta-analysis [63]. These new studies suggest that the association of bladder cancer with pioglitazone might be due to ascertainment bias [64].…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…The beneficial effects of pioglitazone on hepatic histology has been reported in steatohepatitis patients with and without T2DM [226][227][228][229]. Weight gain, edema, the development of bladder cancer, and a decrease in bone mineral density are possible concerns with pioglitazone, and this therapy is not widely used [230,231].…”
Section: Evidence For Current Drug Therapiesmentioning
confidence: 99%
“…Interestingly, glitazone types of chemical molecules that are used in the clinical treatment of diabetes mellitus were found to have anti-neuroinflammatory action and neuroprotection through central PPAR-γ agonism ( Swanson et al, 2011 ). Though existing glitazones have exerted neuroprotection, their applicability in various neurodegenerative disorders is still challenging due to their unwanted effects ( Mehtälä et al, 2018 ). In this backdrop, we have developed novel glitazones (G1 and G2) mainly emphasizing on favorable drug likeness, ADME, and toxicity properties while designing without affecting therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two glitazones were predicted to be non-toxic to hepatic cells, to have very high to medium BBB permeation, and to be a non-inhibitor of a metabolic enzyme (CPYD26), which favors the pharmacokinetic properties of the desired glitazones. TOPKAT models for toxicity have shown that these glitazones (G1 and G2) are free from carcinogen and mutagen potential while the carcinogenicity is the serious adverse effect with existing clinical glitazones ( Mehtälä et al, 2018 ). Lipinski’s RO5 assessment also ensures that both the glitazones did not violate the drug likeness properties.…”
Section: Discussionmentioning
confidence: 99%